Influence Of Organizational Climate And Work Discipline On Employee Performance (Survey Of Department Of Education And Culture Of Tasikmalaya Regency) - Salsabila, Aulia Zahra; Yusnita, Rita Tri; Risana, Dudu (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study was to determine the effect of Organizational Climate and Work Discipline on the Performance of the Office of Education and Culture Office of Tasikmalaya Regency. The research method used is a quantitative method with a survey approach to 71 respondents who are employees of the Tasikmalaya district education and culture office. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis using SPSS version 25. Based on data that has fulfilled the validity test, reliability test and classic assumption test. Simultaneously organizational climate and work discipline have a significant effect on employee performance. The test results show that partially organizational climate variables have a significant effect on employee performance, as well as work discipline variables partially have a significant effect on employee performance.